Evaluating Nippon Yusen Kaisha’s Remote Diagnostic Center: An Analysis of End-User Perspectives Among Engine Management-Level Officers - Arranz, Aloysius Gio P. (Future Science / FSH-PH Publications, 2025)
The integration of shore-based diagnostics in maritime operations is reshaping shipboard maintenance and decision-making practices. This study evaluated Nippon Yusen Kaisha’s Remote Diagnostic Center (RDC) from the perspectives of engine management-level officers onboard its vessels. Specifically, it assessed the RDC’s usefulness, clarity, reliability, ease of use, influence on decision-making, and challenges in shipboard integration. A total of 214 respondents, equally divided between Chief Engineers and Second Engineers, participated through a structured survey analysed using descriptive statistics. Findings revealed that the RDC is moderately useful in enhancing data-driven decisions and supporting the Planned Maintenance System (PMS). It assists in detecting abnormalities and promoting condition-based maintenance, though its reports remain supplementary to firsthand inspections. Reports were generally viewed as clear and accessible, but their influence on major decisions was moderate. The study concludes that NYK’s RDC is a reliable support tool with room for improvement. Enhancements in scope, usability, and real-time responsiveness are recommended to maximize operational value in maritime practice.